EVALUASI PROGRAM KAMPUNG TANGGUH WANI JOGO SUROBOYO DI KELURAHAN PRADAH KALIKENDAL KECAMATAN DUKUH PAKIS KOTA SURABAYA - Christina Yovanka; Indah Prabawati (Publika, 2022)
Surabaya City Government through Surabaya Mayor Regulation Number 28 of 2020 concerning Guidelines for the New Normal Order in the Corona Virus Disease 2019 (Covid-19) Pandemic Conditions in the City of Surabaya chapter 32 implementing the Resilient Village Dare To Guard Surabaya Program as an effort to prevent the spread of Covid-19. This program is a step to prevent the spread of Covid-19 within the RW/RT. This research was conducted in Pradah Kalikendal Village, Surabaya City, which is one of the areas with the highest number of positive numbers in the Dukuh Pakis District. The purpose of this study was to describe the evaluation of the Resilient Village Dare To Guard Surabaya Program in Pradah Kalikendal Village, Surabaya City. This type of research is a descriptive study with a qualitative approach using Dunn's evaluation criteria, namely effectiveness, efficiency, adequacy, alignment, and responsiveness with data collection techniques, namely in-depth interviews, participant observation, documentation, and data triangulation. The technique used to analyze the data uses an interactive model consisting of data collection, data condensation, data presentation and ends with concluding. The results of the study indicate that this program has been running following the applicable guidelines. However, there are obstacles in implementing the program, namely the lack of consistency of the RW task force in implementing the program even though it is well structured in the organizational structure and slack supervision which causes a lack of public awareness in implementing health protocols. Suggestions for implementing this program are that so that the program can run consistently, the task force coordinates and directs the task force in each RW to always carry out monitoring and socialization to residents so that they continue to apply health protocols, and continue to carry out comprehensive programs in each RW so that every community/community target groups feel the same benefits Keywords: Covid-19, Evaluation, Resilient Village Dare To Guard Surabaya Program.